Performance Analysis of Machine Learning Models for Hand Gesture Recognition from Electromyographic Signals - Freitas, Lucas Lemos Cerqueira de; Costa Neto, Artur Brederodes da; Germano, Gabriel Lucas Bento; Silva, Maria Fernanda Herculano Machado da; Silva, Rodrigo Santos da; Cordeiro, Thiago Damasceno (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2026)
Amputation of the upper extremity significantly affects human autonomy by compromising motor functionality, limiting the execution of activities of daily living, and reducing the individual’s capacity for independent interaction with the environment. In 2017, more than 57 million people were living with some form of traumatic amputation, approximately 30% involving the upper limbs. In this context, prostheses controlled by surface electromyographic (sEMG) signals are a promising alternative for restoring motor function, using residual muscles’ electrical activity as a control source. However, automatic gesture recognition from sEMG signals remains challenging, due to physiological variability, noise, and the complexity of neuromuscular patterns. This work presents a systematic and reproducible comparative analysis of four supervised classifiers — KNN, Random Forest, SVM, and Multilayer Perceptron — applied to the NinaPro DB5 dataset, with focus on the joint effect of window size and temporal stride on classification performance, a combination rarely explored in the literature. Time-domain feature extraction and sliding-window segmentation were applied to the models. The KNN and RF models achieved the best results, with accuracies exceeding 99% in certain configurations, reinforcing the potential of supervised methods for developing more accessible and responsive robotic prostheses and human-machine interfaces.